ANALISIS MAYSIR PADA TRANSAKSI PERMAINAN CAPIT BONEKA - agus, sri anggraeni (IAIN Parepare, 2024)
Puppet claw game which often occurs in every corner of the city to villages, which is played by all groups, both children and adults, and this game apparently contains